Collaborative Problem Solving and Literacy Practices: A Conversation-Analytic Case Study of Children’s Online Pre-gaming Interaction - Jawhar, Sabria Salama; Amir, Alia; Huq, Rizwan-ul; Stewart, Simon (Social Interaction. Video-Based Studies of Human Sociality, 2024)
Online video gaming has developed from a hobby to a ubiquitous, social and leisure phenomenon. Roblox, a free-to-play, online sandbox platform has thrived in this time, with a substantial global userbase, where the majority of Roblox users are under 16 years old. Using video recorded data from single case, this study examines the ways in which two preteen players collaboratively participate, solve problems, and share strategies during a pre-gaming interaction. The analysis highlights the affordances of this form of online play for social and language learning. Using Multimodal Conversation Analysis, this study explores how participants leverage cooperative learning strategies including mutual scaffolding techniques and fluidity of epistemic participation that includes material ecology, knowledge exchange, joint problem solving, instructing, and help-seeking. The analysis elucidates a relationship between these pre-gaming activities and participants’ utilization of resources for learning related to language, technology, literacy, and teamwork.